Using a Natural User Interface to Enhance the Ability to Interact with Reconstructed Virtual Heritage Environments (Informatica, 2016)
Virtual Reality (VR) techniques are used to create computer-simulated environments which enable new forms of cultural entertainment. One critical problem is how to design the 3D virtual environments (VE) and what methods should be used for interaction, in order to offer an entertaining experience in an open approach.  This paper focuses on the added value of gaming methods for 3D reconstruction and interaction with 3D representations of cultural heritage assets using a NUI designed for games. The impact of game mechanics and interaction was investigated by developing a VE of a medieval burg (Brasov, Transylvania). The VE development involves high quality 3D reconstruction of the burg, creating a collection of gestures to interact with the VE, and their implementation and testing within the VE. The paper also includes a qualitative and quantitative evaluation of the implemented system, as tested by subjects who carried out a navigation session in the VE.